Cold Antisolvent Bathing Derived Highly Efficient Large‐Area Perovskite Solar Cells. Issue 36 (7th August 2019) - Jang, Gyumin; Kwon, Hyeok‐Chan; Ma, Sunihl; Yun, Seong‐Cheol; Yang, Hyunha; Moon, Jooho
Abstract: Scaling large‐area solar cells is in high demand for the commercialization of perovskite solar cells (PSCs) with a high power‐conversion efficiency (PCE). However, few roll‐to‐roll‐compatible deposition methods for the formation of highly oriented uniform perovskite films are reported. Herein, a facile cold antisolvent bathing approach compatible with large‐area fabrication is introduced. The wet precursor films are submerged in a cold antisolvent bath at 0 °C, and the retarded nucleation and growth kinetics allow highly oriented perovskite to be grown along the [110] and [220] directions, perpendicular to the substrate. The high degree of the preferred crystal orientation benefits the effective charge extraction and reduces the amount of inter‐ and intra‐grain defects inside the perovskite films, improving the PCE from 16.48% (ambient‐bathed solar cell) to 18.50% (cold‐bathed counterpart). The cold antisolvent bathing method is employed for the fabrication of large‐area (8 × 10 cm 2 ) PSCs with uniform photovoltaic device parameters, thereby verifying the scale‐up capability of the method. Abstract : A temperature‐tuned antisolvent bathing method is introduced for fabricating highly oriented and large‐grain perovskite thin films. Using large‐area compatible cold antisolvent bathing, a high‐quality perovskite film is obtained with a reduced defect density and an enhanced charge‐carrier extraction capability, which achieves a champion power‐conversion efficiency of 18.50%.